Memantine protects blood–brain barrier integrity and attenuates neurological deficits through inhibiting nitric oxide synthase ser1412 phosphorylation in intracerebral hemorrhage rats: involvement of peroxynitrite-related matrix metalloproteinase-9/NLRP3 inflammasome activation. Issue 3 (3rd February 2021) - Chen, Xiaowei; Xiang, Xu; Xie, Teng; Chen, Zhijun; Mou, Yu; Gao, Zixu; Xie, Xun; Song, Min; Huang, Hui; Gao, Ziyun; Chen, Min
Abstract : Memantine has demonstrated beneficial effects on several types of brain insults via therapeutic mechanisms mainly related to its activity as a receptor antagonist of N-methyl-D-aspartate. However, the influences of memantine on intracerebral hemorrhage (ICH) remain obscure. This research probed into the neurovascular protective mechanisms of memantine after ICH and its impacts on neuronal nitric oxide synthase (nNOS) ser 1412 phosphorylation. ICH model was established by employing intrastriatal collagenase injection in rats. After modeling, rats were then allocated randomly into sham-operated (sham), vehicle-treated (ICH+V), and memantine-administrated (ICH+M) groups. Memantine (20 mg/kg/day) was intraperitoneally administered 30 min after ICH and thenceforth once daily. Rats were dedicated at 0.25, 6, 12, 24 h, 3 and 7 d post-ICH for measurement of corresponding indexes. Behavioral changes, brain edema, levels of nNOS ser 1412 phosphorylation, peroxynitrite, matrix metalloproteinase (MMP)-9, NLRP3, IL-1β and numbers of dying neurons, as well as the cellular localization of gelatinolytic activity, were detected among the groups. Memantine improved the neurologic deficits and mitigated brain water content, levels of MMP-9, NLRP3, IL-1β and dying neurons. Additionally, treatment with memantine also reduced nNOS ser 1412 phosphorylation and peroxynitrite formation compared with the ICH+V group at 24 h after ICH. In situ zymography simultaneously revealed that gelatinase activity was primarily colocalized with vessel walls and neurons. We concluded that memantine ameliorated blood–brain barrier disruption and neurologic dysfunction in an ICH rat model. The underlying mechanism might involve repression of nNOS ser 1412 phosphorylation, as well as peroxynitrite-related MMP-9 and NLRP3 inflammasome activation. Abstract : Supplemental Digital Content is available in the text.